A surgical study of serological markers such as C-reactive protein and interleukin 6 in response to postoperative infection in patients with open fractures in a tertiary care hospital - Jebaraj, J. P. V.; Rajan, B. Ezhil; Viswanath, N. Ashok; Preethy, R. (International Journal of Research in Orthopaedics, 2022)
To study the response of C-reactive protein (CRP) and interleukin-6 (IL-6) to postoperative infection in patients with open fractures. Thirty patients with open fractures of extremities within 12 hours of injury were included in study. Blood samples were collected for Postoperative infection is a devastating complication of open fractures. The ideal investigation for early diagnosis of infection should be done before surgery and should be accurate, convenient to patient, cause minimal morbidity. Test such as CRP and IL-6 estimation is utilized in this study. CRP and IL 6 estimation on admission, second and fourth post-op day. All patients underwent surgery and reports evaluated. It was observed that CRP peak on post-op day 4 and IL 6 on postoperative day 2 in patients with infection before clinical evidence of infection. This prospective study includes 30 cases, followed up in ward for a week. Various factors regarding clinical presentation, findings of various investigations, operative treatment had been analyzed. The sensitivity of CRP in our study was 100%, and specificity was 42%. The persistent rise of CRP value seen within the infected group was statistically significant (p<0.05). The present clinical study of estimation of CRP and IL 6 to detect postoperative infection in patients after open fractures is an excellent diagnostic test for early detection and management of infection.